Resilience and sustainability of social enterprises: a systematic review and bibliometrics using PRISMA - Prashant Salwan; Suchitra Ajgaonkar; Netra Neelam; Rama Venkatachalam (Cogent Social Sciences)
Purpose Social enterprises (SE) face unique challenges and tensions that require resilience and business sustainability efforts to survive and grow. Therefore, authors perform a PRISMA based systematic literature review (SLR) that provides specific organizational practices constructed from the themes derived through the study. It also critically analyses this data and enables SE practitioners to build resilience and foster business sustainability.Methodology This study performed bibliometric analysis on 1743 articles from all journals indexed in Scopus and Web of Science. This study systematically analyzed 257 journal articles from reputed journals to elaborate and classify SE resilience and/or sustainability practices.Findings and Implications Eleven clusters were developed following a systematic review process: economic and social effects, entrepreneurship, financial sustainability, hybridity management, bricolage, social impact, social network, social innovation, strategic orientation, digital technology and institutional support. Social entrepreneurs and managers will find meaningful conversations in the findings. Research gaps are delineated as one of the outcomes of this study.Originality There are such reviews on for-profit or commercial businesses, but they are missing in the SE literature.